2023
DOI: 10.1101/2023.05.15.540828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of 3-Cyano-7-cyclopropylamino-pyrazolo[1,5-a]pyrimidines Toward the Development of an In Vivo Chemical Probe for CSNK2A

Abstract: 3-cyano-7-cyclopropylamino-pyrazolo[1,5-a]pyrimidines, including the chemical probe SGC-CK2-1, are potent and selective inhibitors of CSNK2A in cells but have limited utility in animal models due to their poor pharmacokinetic properties. While developing analogs with reduced intrinsic clearance and the potential for sustained exposure in mice, we discovered that Phase II conjugation by GST enzymes was a major metabolic transformation in hepatocytes. A protocol for co-dosing with ethacrynic acid, a covalent rev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…B1 proved to be very tolerant to microsomal exposure, demonstrated excellent stability (>85%) after 30 min, and was not prone to non-NADPH-dependent enzymatic degradation. This stability is not true for other kinase inhibitor scaffolds, which are significantly degraded after just 30 min ( Yang et al, 2023 ). Since compound B1 was found to have the required aqueous solubility and mouse liver microsomal stability, it was submitted for in vivo characterization.…”
Section: Resultsmentioning
confidence: 99%
“…B1 proved to be very tolerant to microsomal exposure, demonstrated excellent stability (>85%) after 30 min, and was not prone to non-NADPH-dependent enzymatic degradation. This stability is not true for other kinase inhibitor scaffolds, which are significantly degraded after just 30 min ( Yang et al, 2023 ). Since compound B1 was found to have the required aqueous solubility and mouse liver microsomal stability, it was submitted for in vivo characterization.…”
Section: Resultsmentioning
confidence: 99%
“…These efforts led to the identification of compound 6 (Figure 5), which exhibited potent antiviral activity with moderate rates of clearance in human primary hepatocytes. 55 The X-ray crystal structure compound 3 in the ATP binding site of CK2 [PDB ID 6Z83, Figure 6] indicated that the pyrazolopyrimidine core and 7-cyclopropylamine bind to Val116 in the hinge region. The propionamide group formed two H-bonds with the amino acid residues Lys68 and Asp175.…”
Section: ■ Ck2 Inhibitorsmentioning
confidence: 99%